Examining the Undocumented College Student Policy Implementation Environment Through a Contextual Interaction Theory Lens. (December 2021) - Nienhusser, H. Kenny; Connery, Chelsea
The higher education policy implementation landscape has substantially shaped postsecondary education opportunities for undocumented youth, who are already negatively affected by discriminatory public policies, and institutional agents, who are often unprepared to address their needs. Guided by Bressers's contextual interaction theory that identifies the role of contexts, actor characteristics, and social interactions among implementers in the policy implementation process, the researchers examined the experiences of 45 community college administrators in four states to understand how these elements shaped the participants' role as implementers of policies for undocumented students. Implications are significant given current social and political landscapes and challenges higher education institutional agents encounter in implementing policies that affect undocumented students' educational opportunities.